2020
DOI: 10.1016/j.neucom.2019.08.093
|View full text |Cite
|
Sign up to set email alerts
|

Deep online hierarchical dynamic unsupervised learning for pattern mining from utility usage data

Abstract: While most non-intrusive load monitoring (NILM) work has focused on supervised algorithms, unsupervised approaches can be more interesting and practical. Specifically, they do not require labelled training data to be acquired from the individual appliances and can be deployed to operate on the measured aggregate data directly. We propose a fully unsupervised novel NILM framework based on Dynamic Bayesian hierarchical mixture model and Deep Belief network (DBN). The deep network learns, in unsupervised fashion,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Furthermore, as more experiments were conducted, it was found that grid cells, such as neurons, may also be present in the neocortex [21,22]. The memory-prediction framework has been implemented in various fields, including object identification [23,24], medicine [25], online learning [26,27], real-time network traffic anomaly detection [28][29][30][31], and network forensics [32].…”
Section: Related Workmentioning
confidence: 99%
“…Furthermore, as more experiments were conducted, it was found that grid cells, such as neurons, may also be present in the neocortex [21,22]. The memory-prediction framework has been implemented in various fields, including object identification [23,24], medicine [25], online learning [26,27], real-time network traffic anomaly detection [28][29][30][31], and network forensics [32].…”
Section: Related Workmentioning
confidence: 99%
“…Applying statistical models and methods to such big data can cause excessive computational burden not only in terms of strains on computer memory due to the large volume but also strains in terms of computational efficiency since even seemingly very simple tasks can take an inordinate amount of time to compute. In a recent review, [31] grouped the statistical and computational methodologies into three categories: subsampling-based approaches (e.g., [35,40; 34]), divide and conquer approaches (e.g., [23]; [18]; [1]; [16]; [17]), and online updating approaches (e.g., [27]; [24]; [28]; [26]). Online updating approaches are distinct from the other two because they target problem where data arrive in streams or large chunks and address statistical problems in an updating framework without storage requirements for previous data.…”
Section: Introductionmentioning
confidence: 99%